Accessibility of 2019 Election Logistics (Study: Procurement and Distribution of Election Logistics in Riau Province) - Novendra Hidayat; Andika Kurnia Putra; Bela Sintiya; Cindy Guswanti; Novri Elferida Sihotang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
This study discusses the Procurement and Distribution of 2019 Election Logistics in Riau Province, Election Logistics has a central and strategic role as one of the aspects that determines the success of the election. The process included in the Election Logistics Distribution is the process of sending, receiving and withdrawing logistics. Based on the results of the 2019 Legislative election evaluation in the General Election Commission and the facts on the ground that there are weaknesses and shortcomings to the distribution process and monitoring of the 2019 Election Logistics in Riau. These shortcomings and weaknesses result in late ballot papers for people who will participate in voting. Through the Framing analysis approach, this research explains that Logistics Procurement and Distribution is still constrained by mechanisms that have not integrated technology such as the availability of Procurement and Distribution that are offline. Therefore, the Election Logistics Accessibility mechanism needs to be designed with an online model using information technology.